2019
DOI: 10.1002/hep.30288
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Human Pluripotent Stem Cells for Modeling Liver Development and Disease

Abstract: The use of pluripotent stem cells (PSCs) has transformed the investigation of liver development and disease. Clinical observations and animal models have provided the foundations of our understanding in these fields. While animal models remain essential research tools, long experimental lead times and low throughput limit the scope of investigations. The ability of PSCs to produce large numbers of human hepatocyte‐like cells, with a given or modified genetic background, allows investigators to use previously i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 74 publications
(141 reference statements)
0
20
0
Order By: Relevance
“…For example, the extent of molecular and biochemical analyses that can be performed on these models is limited by the amount of material. Fortunately, the directed differentiation of human pluripotent stem cells has emerged as an alternative model for the study of cell fate [26,27]. Several research groups have demonstrated that cells that share many characteristics with human hepatocytes can be generated from human embryonic (hESCs) and induced pluripotent (hiPSCs) stem cells [28,29,30,31,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the extent of molecular and biochemical analyses that can be performed on these models is limited by the amount of material. Fortunately, the directed differentiation of human pluripotent stem cells has emerged as an alternative model for the study of cell fate [26,27]. Several research groups have demonstrated that cells that share many characteristics with human hepatocytes can be generated from human embryonic (hESCs) and induced pluripotent (hiPSCs) stem cells [28,29,30,31,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods were developed to generate organoids from iPSCs, and most protocols attempt to recapitulate the developmental stages of hepatogenesis . The details of hepatic differentiation protocols were reviewed recently . We reported a complex method to generate liver organoids from iPSCs by coculturing with vascular stem cells and mesenchymal stem cells .…”
Section: Methods Of Liver Organoid Generationmentioning
confidence: 99%
“…The possibility to convert hiPSCs into functional hepatocytes allows for novel opportunities in assay development and holds great potential for future pre-clinical and regenerative medicine applications. For example, hiPSC derived from patients suffering from, e.g., inherited metabolic diseases can be used for modeling these types of diseases in vitro [11][12][13]. Combining the hiPSC technology with the constantly progressing genome editing technologies, e.g., CRISPR-Cas9, further increases the potential for disease modeling and therapeutic applications [14,15].…”
Section: Introductionmentioning
confidence: 99%